INVENTARISASI SERANGGA PADA PERKEBUNAN KAKAO (THEOBROMA CACAO) LABORATORIUM UNIT PERLINDUNGAN TANAMAN DESA BEDULU, KECAMATAN BLAHBATUH, KABUPATEN GIANYAR, BALI - PUTRA, I. G. A. PRADANA; WATINIASIH, NI LUH; SUARTINI, NI MADE (Jurnal Biologi Udayana, 2011)
Bali has the potency to grow plantation, particularly cacao plants (Theobroma cacao). The increase of cacao production is supported by the increase of the number of productive cacao plants, but the production rate per hectare per year decreased at some districts. One reason of the decreasing cacao production was due to the attack of Plant Disease Organism. This research aimed to investigate the insect families associated with cacao plantations and the fuctions of the insects on cacao plants, at Bedulu Village, District of Blahbatuh, Gianyar Regency. Samples were collected from January to February 2011 and insect identification was conducted for two months at Animal Taxonomy Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Udayana University. Field sample collections were arranged by randomized sampling techniques that the block samples were chosen randomly. Samples were collected with beating technique and trapping with sex pheromone. All insects collected from the field belong to eight groups/types. The highest percentage of insect type collected fuctioned as vector (56.1%) and the lowest was acted as parasites (0.1%). The highest number of two groups insects captured were groups of pests and predators. The insect that function as biological control was the family of Labiduridae, Anthocoridae, Reduviidae, Chrysopidae, Gryllidae and Chalcididae.
Keywords: Bali; cacao; insect; plant disease organism